Molecular bases of circadian rhythmicity in renal physiology and pathology - Bonny, Olivier (Oxford University Press, 2013)
The physiological processes that maintain body homeostasis oscillate during the day. Diurnal changes characterize kidney functions, comprising regulation of hydro-electrolytic and acid-base balance, reabsorption of small solutes and hormone production. Renal physiology is characterized by 24-h periodicity and contributes to circadian variability of blood pressure levels, related as well to nychthemeral changes of sodium sensitivity, physical activity, vascular tone, autonomic function and neurotransmitter release from sympathetic innervations. The circadian rhythmicity of body physiology is driven by central and peripheral biological clockworks and entrained by the geophysical light/dark cycle. Chronodisruption, defined as the mismatch between environmental–social cues and physiological–behavioral patterns, causes internal desynchronization of periodic functions, leading to pathophysiological mechanisms underlying degenerative, immune related, metabolic and neoplastic diseases. In this review we will address the genetic, molecular and anatomical elements that hardwire circadian rhythmicity in renal physiology and subtend disarray of time–dependent changes in renal pathology.